A selectable all-in-one CRISPR prime editing piggyBac transposon allows for highly efficient gene editing in human cell lines - Reto Eggenschwiler (Nature Portfolio, 2021)
Abstract CRISPR prime-editors are emergent tools for genome editing and offer a versatile alternative approach to HDR-based genome engineering or DNA base-editors. However, sufficient prime-editor expression levels and availability of optimized transfection protocols may affect editing efficiencies, especially in hard-to-transfect cells like hiPSC. Here, we show that piggyBac prime-editing (PB-PE) allows for sustained expression of prime-editors. We demonstrate proof-of-concept for PB-PE in a newly designed lentiviral traffic light reporter, which allows for estimation of gene correction and defective editing resulting in indels, based on expression of two different fluorophores. PB-PE can prime-edit more than 50% of hiPSC cells after antibiotic selection. We also show that improper design of pegRNA cannot simply be overcome by extended expression, but PB-PE allows for estimation of effectiveness of selected pegRNAs after few days of cultivation time. Finally, we implemented PB-PE for efficient editing of an amyotrophic lateral sclerosis-associated mutation in the SOD1-gene of patient-derived hiPSC. Progress of genome editing can be monitored by Sanger-sequencing, whereas PB-PE vectors can be removed after editing and excised cells can be enriched by fialuridine selection. Together, we present an efficient prime-editing toolbox, which can be robustly used in a variety of cell lines even when non-optimized transfection-protocols are applied.